Remarkable Geographic Structuring of Rheophilic Fishes of the Lower Araguaia River - Hrbek, Tomas; Meliciano, Natasha V.; Zuanon, Jansen; Farias, Izeni P. (Frontiers in Genetics, 2018)
Rapids and waterfalls, and their associated fauna and flora are in peril. With the construction of each new hydroelectric dam, more rapids and waterfalls are destroyed, leading to the disappearance of associated fauna and flora. Areas of rapids harbor distinct, highly endemic rheophilic fauna and flora adapted to an extreme environment. Rheophilic habitats also have disjunct distribution both within and across rivers. Rheophilic habitats thus represent islands of suitable habitat separated by stretches of unsuitable habitat. In this study, we investigated to what extent, if any, species of cichlid and anostomid fishes associated with rheophilic habitats were structured among the rapids of Araguaia River in the Brazilian Amazon. We tested both for population structuring as well as non-random distribution of lineages among rapids. Eight of the nine species had multiple lineages, five of these nine species were structured, and three of the eight species with multiple lineages showed non-random distribution of lineages among rapids. These results demonstrate that in addition to high levels of endemicism of rheophilic fishes, different rapids even within the same river are occupied by different lineages. Rheophilic species and communities occupying different rapids are, therefore, not interchangeable, and this realization must be taken into account when proposing mitigatory/compensatory measures in hydroelectric projects, and in conservation planning.